The Effect of Montessori Counting Stick Media on Student Learning Outcomes in Addition and Subtraction Material for First-Grade Students of SD Negeri 17 Sitiung - Filahanasari, Eka; Putri, Dhara Atik; Munawaroh, Reti (The Future of Education Journal, 2025)
This research is motivated by the results of observations during the implementation of the School Field Introduction Program (PLP) at SDN 17 Sitiung, which showed low mathematics learning outcomes of grade I students, especially in addition and subtraction materials. The low learning outcomes are caused by the lack of utilization of interesting learning media that are in accordance with the characteristics of elementary school students. Therefore, this study aims to improve students' mathematics learning outcomes through the use of Montessori counting stick media. The study used a quantitative approach with a One-Group Pretest-Posttest Design. The subjects of the study were 12 grade I students of SDN 17 Sitiung. The data collection instrument was in the form of tests, namely pretest and posttest, which were used to measure initial abilities and after treatment. The average pretest score of students was 52.64. After treatment in the form of using Montessori counting stick media, the average posttest score increased to 83.33. Data analysis was carried out using the Paired Sample T-Test. The results of the analysis showed a significance value of 0.000 (p < 0.05), which means there is a significant difference between the pretest and posttest results. This indicates that the use of Montessori counting stick media has a positive effect on improving students' mathematics learning outcomes. This increase occurs because the counting stick media is able to attract students' attention, arouse their enthusiasm for learning, and help them understand the concept of addition and subtraction in a concrete and enjoyable way. With an approach that is in accordance with students' cognitive development, the learning process becomes more effective. In conclusion, the Montessori counting stick media has proven effective in improving the mathematics learning outcomes of grade I students of SDN 17 Sitiung on the addition and subtraction material.